How should we counter challenges in teaching pronunciation for EIL? - Nangimah, Musrifatun (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2020)
English as an international language (EIL) deals with the use of English in wider communication both global and local contexts. In an EIL context, people with different mother tongue (L1) use English to share ideas and culture. That is why intelligible English which should be no longer norm-bound is needed. Teaching pronunciation for EIL, especially should provide variety of English accents. English teachers should be flexible to the modification needed and fully informed of what, why, and how to teach and assess comprehensible English. Unfortunately, teaching English pronunciation has always been challenging for non-native English speaker teachers. In this retrospective essay, I discussed the challenges of teaching English pronunciation: the differences between English and students’ L1 phonological system, teachers’ strong and long-standing belief about unnecessary pronunciation, teachers’ excessive workload and insufficient teaching materials, and teachers’ lack of confidence due to native speaker preference model. Ideas to think about and a simple lesson plan to teach English pronunciation that is suitable for EIL context are provided.